Navigating the Transformative Impact of Artificial Intelligence in Health Services Research - Guosong Wu; Fengjuan Yang (Health Science Reports)
ABSTRACT Background and Aims Artificial intelligence (AI) is transforming health services research by providing novel insights, enhancing care quality, and improving patient outcomes. This review sought to assess AI's impact on health services research, highlighting its applications, benefits, and associated challenges. Methods We conducted a comprehensive review of recent literature on AI applications in health services research. Key areas of focus included image processing and language processing. The review also addressed the ethical and practical challenges of integrating AI into healthcare. Results Over the past decade, AI‐related research has markedly increased. AI has significantly advanced health services research by improving diagnostic precision, care quality, decision‐making, hospital operations, and personalized care. The benefits of AI in image processing and language processing have been substantial, resulting in positive impacts on healthcare practices. However, integrating AI into healthcare presents considerable ethical and practical challenges, including the need for robust data security, the mitigation of algorithmic biases, and the achievement of interoperability among diverse data systems. Conclusions AI offers significant potential to advance health services research and enhance patient care through powerful applications in image processing, language processing, diagnostic precision, decision‐making, and hospital operations. By leveraging AI's capabilities, healthcare systems can achieve more personalized, efficient, and accurate care. Addressing key challenges is essential for the effective and equitable integration of AI into healthcare systems.